643. Coronary Artery Aneurysms Are Found on Blindly Read Echocardiograms From Febrile Patients with and Without Kawasaki Disease. (26th November 2018) - Desai, Kinjal; Rabinowitz, Edon J; Mitchell, Elizabeth; Hayes, Denise; Tugertimur, Aykut; Kwon, Elena; Dhanantwari, Preeta; Misra, Nilanjana; Rubin, Lorry
Abstract: Background: In 2017, the American Heart Association published new Kawasaki disease (KD) guidelines including echocardiographic (echo) criteria for diagnosis of incomplete KD (iKD). Echo is positive if 1 or more coronary arteries (CA) show aneurysmal dilation ( Z score of ≥ 2.5), or if a CA has milder dilation ( Z score of 2–2.49) plus ≥2 of the following: decreased left ventricular function, mitral regurgitation, and pericardial effusion. While CA dilation is seen commonly in KD and iKD, specificity of this finding is unclear because patients with systemic febrile illnesses may have CA dilation. To assess specificity of the American Heart Association criteria, blinded readers measured CA dimension in patients with KD and iKD and in febrile and healthy patient controls. Methods: This is a single-center retrospective study. De-identified echo clips of CA from patients age 0–10 years were interpreted blindly and independently by six pediatric cardiologists. KD and iKD diagnoses were based on clinical data and IVIG treatment. Control groups were healthy patients evaluated for a benign murmur and febrile patients with fever ≥72 hours without a KD diagnosis or IVIG treatment. Detection of left ventricular dysfunction, mitral regurgitation and effusion was recorded. An echo was considered positive if the reading from at least one reader met AHA criteria for iKD. Results: Echos from 29 KD, 30 iKD, 28 febrile, and 27 healthy patients were reviewed. The initial echo of 41% of KD and 43% of iKD groups met echo criteria for diagnosis of iKD and 55% and 57%, respectively, had CA dilation or aneurysm. Among febrile patients, 7 (25%) had an abnormal CA size of which 4 (14%) met echo criteria for iKD. In the healthy patients, four (15%) had abnormal CA of which two (7.4%) met echo criteria for iKD. Among patients with a positive echo read, the median number of readers who read a CA as dilated was similar for each group. Furthermore, of all patients meeting echo criteria for iKD, 90% had aneurysmal CA dilatation. Conclusion: Although CA abnormalities diagnostic of KD were commonly present at time of diagnosis in patients with KD or iKD, these findings were also present in some healthy and some febrile patients. Diagnosis of iKD in febrile children using echo criteria may result in an over-diagnosis of KD. Disclosures: All authors: No reported disclosures.